I2‐Catalyzed Intermolecular Cyclization to Synthesis of 3‐Acylated Indolizines. Issue 42 (16th November 2020) - Zheng, Jing; Chen, Linli; Liu, Xiaojuan; Xu, Wenju; Wang, Yan; He, Qin; Liu, Hanqing; Ye, Min; Luo, Guotian; Chen, Zhengwang
Abstract: Indolizine is one of the important nitrogen containing heterocycles due to their wide range of bioactivities. A convenient and efficient intermolecular cyclization reaction catalyzed by I2 was developed, affording 3‐acylated indolizines in good to excellent yields. 2‐Pyridylacetonitrile, 2‐pyridylacetone and 2‐pyridylacetamides were all compatible, and water was considered as the source of the carbonyl oxygen in the products. Furthermore, the conjugated enynenitriles were afforded from 2‐pyridylacetonitrile with ynals in high yields. Abstract : Indolizine is one of the important nitrogen containing heterocycles due to their wide range of bioactivities. A convenient and efficient intermolecular cyclization reaction catalyzed by I2 was developed, affording 3‐acylated indolizines in good to excellent yields.2‐Pyridylacetonitrile, 2‐pyridylacetone and 2‐pyridylacetamides were all compatible, and water was considered as the source of the carbonyl oxygen in the products. Furthermore, the conjugated enynenitriles were afforded from 2‐pyridylacetonitrile with ynals in high yields.